2014
DOI: 10.1186/1744-8069-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Artemin Growth Factor Increases Nicotinic Cholinergic Receptor Subunit Expression and Activity in Nociceptive Sensory Neurons

Abstract: BackgroundArtemin (Artn), a member of the glial cell line-derived growth factor (GDNF) family, supports the development and function of a subpopulation of peptidergic, TRPV1-positive sensory neurons. Artn (enovin, neublastin) is elevated in inflamed tissue and its injection in skin causes transient thermal hyperalgesia. A genome wide expression analysis of trigeminal ganglia of mice that overexpress Artn in the skin (ART-OE mice) showed elevation in nicotinic acetylcholine receptor (nAChR) subunits, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 63 publications
(100 reference statements)
3
28
2
Order By: Relevance
“…Taken together, our results showed that α 5 -null mice exhibited impaired development of hyperalgesia and allodynia after inflammatory injury, namely that elicited by carrageenan or CFA, suggesting the importance of α 5 *-nAChRs as a target for the treatment of both acute and chronic inflammatory pain. Interestingly, intraplantar injection of CFA in the mouse was recently reported to increase the dorsal root ganglia (DRG) levels of α 3 and β 4 mRNAs [35]. While changes in the levels of α 5 mRNAs were not reported in this study, it is possible that peripheral α 5 -containing nAChRs in DRGs contribute to nicotine anti-inflammatory and antinociceptive actions, and that α 5 -containing nAChRs (possibly α 3 α 5 β 4 *) in the DRGs undergo plasticity during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results showed that α 5 -null mice exhibited impaired development of hyperalgesia and allodynia after inflammatory injury, namely that elicited by carrageenan or CFA, suggesting the importance of α 5 *-nAChRs as a target for the treatment of both acute and chronic inflammatory pain. Interestingly, intraplantar injection of CFA in the mouse was recently reported to increase the dorsal root ganglia (DRG) levels of α 3 and β 4 mRNAs [35]. While changes in the levels of α 5 mRNAs were not reported in this study, it is possible that peripheral α 5 -containing nAChRs in DRGs contribute to nicotine anti-inflammatory and antinociceptive actions, and that α 5 -containing nAChRs (possibly α 3 α 5 β 4 *) in the DRGs undergo plasticity during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time RT-PCR was performed as described previously [27]. Total RNA was isolated from the hippocampus with TRIzol reagent (Invitrogen, Camarillo, CA) and reversetranscribed into cDNA using a Prime Script RT reagent kit (Takara, Dalian, China) for quantitative PCR (ABI Step One Plus, Foster City, CA) in the presence of a fluorescent dye (SYBR Green I; Takara, Dalian, China).…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…The relative expression of genes was determined using the 2 −ΔΔct method with normalization to GAPDH expression. The primers used for α7nAChR were 5′-CACATTCCACACCAACGTCTT-3′ and 5′-AAAAGGGAACCAGCGTACATC-3′ [27]; the p r i m e r s f o r n A C h R s u b u n i t α 4 w e r e 5 ′ -C A G C T T C C A G T G T C A G A C C A -3 ′ a n d 5 ′ -TGGAAGATGTGGGTGACTGA-3′ [28]; the primers for β2nAChR were 5′-GAGGTGAAGCACTTCCCATTT-3′ and 5′-GCCACATCGCTTTTGAGCAC-3′ [27]; the primers for AP-2α subunit were 5′-TCCTTACTCCCACGTCAACG-3′ and 5′-TGTACTTCGAGGTGGAGCTG-3′ [29]; the primers for GAPDH were 5′-TGGGTGTGAACCACGAG-3′ and 5′-AAGTTGTCATGGATGACCTT-3′.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…There is also evidence that the algesic effects of nicotine may be mediated via the activation of TRPA1 rather than nAChRs (Talavera et al, 2009), raising doubt as to whether any of the nociceptive actions of nicotine are mediated through nAChRs. However, this last study relied on the use of heterologous expression systems and mouse DRG neurons, and it is becoming increasingly clear that there are species differences in the density and distribution of nAChRs, where, for example, currents are detected in >60% of rat DRG neurons (Genzen et al, 2001, Dube et al, 2005, Hone et al, 2012) but less than 20% of mouse DRG neurons (Talavera et al, 2009, Albers et al, 2014). Thus, it remains to be determined whether nAChRs underlie the algesic vs analgesic actions of nicotine on cutaneous afferents.…”
mentioning
confidence: 99%
“…Unless this is a feedback-inhibitory mechanism that counters a number of well-described changes that contribute to an increase in afferent excitability, for a decrease in nAChRs to contribute to neuropathic pain, one would have to conclude that nAChRs normally function to decrease afferent excitability. However, we have recently observed in the mouse that the neurotrophic factor artemin drives an increase in nAChR subunit expression which is associated with an increase in both the density and distribution of nAChR currents in mouse sensory neurons (Albers et al, 2014). Furthermore, given evidence that artemin is increased in peripheral tissue in the presence of inflammation, and artemin-induced hyperalgesia can be attenuated with peripheral administration of the nAChR antagonist hexamethonium (Albers et al, 2014), our results suggest that in the presence of inflammation, nAChR signaling may be pro-nociceptive.…”
mentioning
confidence: 99%